The gospel of climate skepticism: why evangelical Christians oppose action on climate change - Veldman, Robin Globus (University of Californiarnia Press, 2019)
The end-time apathy hypothesis -- Practical environmentalism -- End-time beliefs and climate change -- The embattled mentality and climate skepticism -- How evangelical subcultural identity sustains climate skepticism -- Salt and light: skeptical environmental stewards of the Southern Baptist Convention -- Preaching the gospel of climate skepticism -- Awakening the sleeping giant.